Rhetorical Moves in Saint-Exupéry’s The Little Prince: A Genre Analysis - Tanusy, Jeanyfer; Tanto, Trisnowati (Insaniyat: Journal of Islam and Humanities, 2025)
This study investigates the rhetorical structure of Antoine de Saint-Exupéry’s The Little Prince through the lens of genre analysis. Drawing on Swales’ and Bhatia’s frameworks, it applies rhetorical move theory, typically used in academic discourse analysis to a literary narrative. The study addresses three questions: first, what rhetorical moves and steps are present in The Little Prince? second, how do these moves contribute to the narrative and thematic development? third, what communicative purposes do these moves serve within the context of children’s literature? The analysis adopts a qualitative approach, in which each chapter of the novel was examined through close reading and move identification based on structural and thematic cues. Findings show a consistent pattern of Complication and Resolution across the chapters, with other moves such as Abstract and Coda used more selectively to shape reader interpretation. This research contributes to genre studies by extending rhetorical move analysis to narrative fiction, offering a bridge between ESP traditions and literary discourse. The findings also support educators and curriculum designers in teaching narrative structure and rhetorical awareness in literature classrooms.